2019
DOI: 10.3390/ijerph16183308
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Bacterial and Fungal Aerosols: Microorganism Indices in A Waste-Sorting Plant in Poland

Ewa Brągoszewska

Abstract: An increased understanding of airborne microorganism populations should enable a better interpretation of bioaerosol exposure found in a working environment. An assessment of the contamination levels of mesophilic bacterial aerosol (MBA) and fungal aerosol (FA) was carried out using two evaluation indices for microbiological pollution—the total index of microbiological contamination per cubic meter (TIMC/m3) and the indoor–outdoor index (IOI). An advantage of selected indices is the inclusion of several co-exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…It is important to reduce and control the concentrations of harmful microorganisms in the air, to ensure good air quality. Several studies [17][18][19] have indicated that an important aspect in the work environment is the efficiency of the ventilation system and suggested associations among sources, risk factors, and transmission of microorganisms in the hospital and that air cleaning could decrease the concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to reduce and control the concentrations of harmful microorganisms in the air, to ensure good air quality. Several studies [17][18][19] have indicated that an important aspect in the work environment is the efficiency of the ventilation system and suggested associations among sources, risk factors, and transmission of microorganisms in the hospital and that air cleaning could decrease the concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies showed seasonality is a factor controlling airborne bacterial emissions and community composition [ 52 , 54 57 ]. In agreement with the above, our results reveal a diverse population of bacteria in Kuwaiti airborne dust that changed over time and between locations.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of bioaerosols on human health is not only related to their concentrations. The aerodynamic diameters of bioaerosols determine their potential to be deposited either in the tracheal, bronchial, or alveolar regions of the lungs, so their size distribution is also important [20,34]. The use of the six-stage Andersen impactor allowed us to obtain data on the grain distribution of micro-organisms and to determine how deeply they penetrate the respiratory system of power plant workers.…”
Section: Particle Size Distribution (Psd) Of Bioaerosolsmentioning
confidence: 99%